2006
DOI: 10.1002/cbf.1313
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in liver tissue of ovariectomized and pinealectomized rats: effect of estradiol and progesterone supplementation

Abstract: The present study aimed to determine the effect of estradiol-progesterone supplementation and pinealectomy on lipid peroxidation of liver tissue in ovariectomized rats. The study was carried out on 36 adult Sprague-Dawley female rats, which weighed 200-250 g. The rats were divided into 6 groups: Group 1: Sham Ovariectomy (Sham-Ovx), Group 2: Ovariectomy (Ovx), Group 3: Ovx + Estradiol-Progesterone supplementation (Ovx + H), Group 4: Sham Pinealectomy and Ovx (Sham Pnx -Ovx), Group 5: Ovx -Pnx, Group 6: Ovx -Pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
3
13
0
2
Order By: Relevance
“…4A, B, C and 5). Accordingly, recent studies have shown that although ovariectomy leads to oxidative damage in liver (Oztekin et al, 2006a) and renal tissue (Oztekin et al, 2006b), female sex hormones (E2 and progesterone) supplementation protect against lipid peroxidation by activating the antioxidant system. In the same line, it has been shown that postmenopausal women tend to have high levels of plasma malondialdehyde (MDA) that are reversed by estrogen replacement therapy (Kumru et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…4A, B, C and 5). Accordingly, recent studies have shown that although ovariectomy leads to oxidative damage in liver (Oztekin et al, 2006a) and renal tissue (Oztekin et al, 2006b), female sex hormones (E2 and progesterone) supplementation protect against lipid peroxidation by activating the antioxidant system. In the same line, it has been shown that postmenopausal women tend to have high levels of plasma malondialdehyde (MDA) that are reversed by estrogen replacement therapy (Kumru et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen by itself is a critical regulator hormone for oxidative stress in that it alters serum lipid concentrations, coagulation and fibrinolytic systems, antioxidant systems and the production of other vasoactive molecules, such as nitric oxide and prostaglandins, all of which can influence the development of vascular disease [5]. It is known that sex hormones are associated with oxidative status and lipid peroxidation (LPO) [6,7,8,9]. Many studies have used ovariectomized rat models to demonstrate the relationship between decreased sex hormones and oxidative stress in various tissues and focused on LPO.…”
Section: Introductionmentioning
confidence: 99%
“…Thema jores tro geninrep ro duc ti onpe ri odoffema lesises tra di ol(E2).Inthestu di escar ri edout,it wassta tedthatinova ri ec to mi zedpa ti entsE2tre -at mentre du cedthein cre a singoxi da ti vestressand func ti o nedasanan ti o xi dantthankstothisfe a ture. 37,38 Phe no licstruc tu reofes tro genwaspo in ted outasare a sonofthisef fect. 39 Yet,onthecon trary, inanex pe ri men talstudyad mi nis te redbyAy di lek etal.itwasex pres sedthatthetes tos te ro ne,which isado mi nanthor mo neinma les,in cre a sedoxi dati vestressanddec re a sedGSH.…”
Section: Discussionunclassified